Menemukan Teologi Leonardo Boff dalam Ensiklik Paus Fransiskus Laudato Si' - Buce A. Ranboki (Indonesian Journal of Theology, 2017)
As a Catholic theologian at the vanguard of liberation theology, Leonardo Boff wrote much about the poor and of the destruction of nature. Boff constructed his theology on the basis of Vatican II’s (1962-1965) spirit of aggiornamento. Eventually, and with much controversy, Boff opted to leave the Franciscan order, having oft-criticized the doctrines and social teachings of the Catholic Church deemed “lukewarm” toward structural poverty and Latin American socio-economic life that had been impacted by the actions of junta militarism; as well, he criticized both the hierarchical spirit of the Roman Catholic Church and the doctrine of papal infallibility. Since the election of Jorge Mario Bergoglio (Pope Francis), who has dedicated his life and theology to address the destruction of nature and the cries of the poor, the spirit of Boff's theology seems again to be on the rise. My conviction is that the theological content of Laudato si’ displays something of a Boffian character, the import of which propels the present study. By way of comparative method, I show that there are similarities in the theologies of both theologians. This essay begins with an exploration of Boff's theology, continuing with an exploration of the text of the encyclical Laudato si’, followed by the bringing together of these texts comparatively. By the end of this paper, a critique concerning the concept of sustainable development will be put forth.